Do Family Environment and Entrepreneurship Learning among Students Contribute to Entrepreneurial Interest through Self Efficacy as an Intervening Variable? - Andika Isma; M. Yusri; Syamsul Bahri; Indah Wati; Adrie Oktavio (Universitas Muhammadiyah Palu, 2024)
This study examines the effect of the family environment and entrepreneurship learning on entrepreneurial interest, with self-efficacy as an intervening variable. The method used in this study is a quantitative method. In this study, we also used a survey method with a questionnaire or Koesener as a data collection instrument. The research population consisted of 427 students in the Faculty of Economics and Business majoring in entrepreneurship. The sampling technique used was a proportional random sampling technique, which was calculated using Slovin with a sample size of 84 respondents or 22% of the total population. The research method used in this study was quantitative. This research showed that self-efficacy, family environment, and entrepreneurial learning affect entrepreneurial interest. If students have self-efficacy, a good family environment, and the desire to experience high entrepreneurial learning, this will also increase their interest in entrepreneurship.